Comparing the Mini-Mental State Examination and the modified Mini-Mental State Examination in the detection of mild cognitive impairment in older adults. (19th July 2018) - Van Patten, Ryan; Britton, Karysa; Tremont, Geoffrey
ABSTRACT: Objectives: To show enhanced psychometric properties and clinical utility of the modified Mini-Mental State Examination (3MS) compared to the Mini-Mental State Examination (MMSE) in mild cognitive impairment (MCI). Design: Psychometric and clinical comparison of the 3MS and MMSE. Setting: Neuropsychological clinic in the northeastern USA. Participants: Older adults referred for cognitive concerns, 87 of whom were cognitively intact (CI) and 206 of whom were diagnosed with MCI. Measurements: The MMSE, the 3MS, and comprehensive neuropsychological evaluations. Results: Both instruments were significant predictors of diagnostic outcome (CI or MCI), with comparable odds ratios, but the 3MS explained more variance and showed improved classification accuracies relative to the MMSE. The 3MS also demonstrated greater receiver operating characteristic area under the curve values (0.85, SE = 0.02) compared to the MMSE (0.74, SE = 0.03). Scoring lower than 95/100 on the 3MS suggested MCI, while scoring lower than 28/30 on the MMSE suggested MCI. Additionally, compared to the MMSE, the 3MS shared more variance with neuropsychological composite scores in Language and Memory domains but not in Attention, Visuospatial, and Executive domains. Finally, 65.5% MCI patients were classified as impaired (scoring ≤1 SD below the mean) using 3MS normative data, compared to only 11.7% of patients who were classified as impaired using MMSE normative data. Conclusions: Broadly speaking, our data strongly favor the widespread substitution of the MMSE with the 3MS in older adults with concerns for cognitive decline.